Tuning Mg Doping and Features of Bone-like Apatite Nanoparticles Obtained via Hydrothermal Synthesis - Pupilli, Federico (Langmuir : the ACS journal of surfaces and colloids, 2024)
Nanocrystalline apatites have been intensively studied for decades, not only for their well-known mimesis of bone apatite but also for applicative purposes, whether as biomaterials for skeletal repair or more recently for a variety of nanomedical applications enabled by their peculiar surface characteristics. Particularly, ion-doped apatites are of great interest because the incorporation of foreign ions in the composition of apatite (nano)crystals alters the bulk and surface properties, modifying their ability to interact with the external environment. This is clearly seen in the physiology of bone tissue, whose mineral phase, a low crystallinity apatitic phase, can dynamically exchange ions with cells, thus driving bone metabolism. Taking bone mineral as a model, the present work describes the development of Mg-doped hydroxyapatite nanoparticles, exploiting hydrothermal synthesis to achieve extents of Mg2+ doping hardly achieved before and using citrate to develop stable apatite colloidal dispersions. Morphological and physicochemical analyses, associated with in-depth investigation of ions populating the apatitic lattice and the nonapatitic surface layer, concurred to demonstrate the cooperative presence of Mg2+ and citrate ions, affecting the dynamic ion retention/release mechanisms. Achieving high Mg2+ doping rates and understanding how Mg doping translates into surface activation of apatite-based nanoparticles is expected to foster the design of novel smart and tunable devices, to adsorb and release ionic species and cargo molecules, with potential innovations in the biomedical field or even beyond, as in catalysis or for environmental remediation